2011
DOI: 10.1523/jneurosci.3829-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ganglioside Antibody-Mediated Activation of RhoA Induces Inhibition of Neurite Outgrowth

Abstract: Anti-ganglioside antibodies (Abs) are strongly associated with axonal forms of Guillain Barré syndrome (GBS). Some studies indicate that these Abs, including those with GD1a reactivity, are associated with poor prognosis and/or incomplete recovery. We recently demonstrated that a disease-relevant anti-ganglioside Ab with GD1a reactivity inhibits axon regeneration after PNS injury in an animal model (Lehmann et al., 2007). An implication of these findings is that anti-GD1a Abs can mediate inhibition of axon reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 72 publications
(115 reference statements)
1
43
0
1
Order By: Relevance
“…Ab treatment for 24 h significantly increased the number of collapsed growth cones. 41 These observations supported the notion that Ab-mediated inhibition of neurite outgrowth is at least partly mediated at the level of growth cones. This idea was further tested in Xenopus spinal neurons in which localized growth cone collapse leads to repulsive response of growth cones.…”
Section: Rhoa and Rock Activation Induce Inhibition Of Neurite Outgrosupporting
confidence: 65%
See 4 more Smart Citations
“…Ab treatment for 24 h significantly increased the number of collapsed growth cones. 41 These observations supported the notion that Ab-mediated inhibition of neurite outgrowth is at least partly mediated at the level of growth cones. This idea was further tested in Xenopus spinal neurons in which localized growth cone collapse leads to repulsive response of growth cones.…”
Section: Rhoa and Rock Activation Induce Inhibition Of Neurite Outgrosupporting
confidence: 65%
“…A gradient of anti-GD1a reactive Abs induced repulsive turning responses of growth cones in this model. 41 Overall, cell cultures and growth cone studies showed that anti-ganglioside Abs mimicked the Animal studies. Our initial studies focused on establishing an animal model in which effects of anti-ganglioside Abs on axon regeneration could be examined.…”
Section: Rhoa and Rock Activation Induce Inhibition Of Neurite Outgromentioning
confidence: 90%
See 3 more Smart Citations